The Role of China’s Pilot Free Trade Zones in Promoting Institutional Innovation, Industrial Transformation and South-South Cooperation - United Nations Conference on Trade; Development (United Nations, 2023)
This publication aims to discuss the genesis, features and performance of the FTZs strategy. It also presents comparative analysis between FTZs and other special economic zones in other economies in the region. Furthermore, the volume examines the role of FTZs in promoting local SDG progress, industrial development, and South-South cooperation through three case studies.